Pengaruh kualitas pelayanan, harga, dan citra merek terhadap kepuasaan pelanggan - Zulkarnaini, Zulkarnaini; Suhardi, Yusuf; Akhmadi, Ali; Darmawan, Arya; Fanindia, Rania (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
This research aims to identify how service quality, price, and brand image impact the satisfaction level of OP Bekasi customers. In order to gather data, a questionnaire that employed a Likert scale was used. The study's population consisted exclusively of Ory Parcel Bekasi customers, and a non-probability sampling technique was employed to select 97 participants. To analyze the data, the researchers utilized various tests, including validity and reliability tests, partial tests, and coefficient of determination tests, conducted using IBM SPSS version 26 software. The study results showed that service quality, price, and brand image significantly influenced the satisfaction level of OP Bekasi customers.